Caracterização funcional da ORF hipotética XAC3407 codificada por Xanthomonas citri subsp. citri - Santos, Bianca da Costa [UNESP] (2018)
Citrus canker is a disease that affects all the commercially important citrus varieties, caused by the Gram-negative bacterium Xanthomonas citri subsp. citri (Xac). Infection generates necrosis in plants, especially in the foliar area, which in severe cases may cause fruit drop, leading to a decrease in production and quality of the fruits. Symptomatic fruits may yet be used by the juice industry; However, they have no use for table market. Citrus canker has no cure, and eradication of infected plants continues to be the best measure to control the spread of the bacterium. Knowledge about the biology of the etiological agent is therefore a good way to devise strategies of disease spread and control. Our group has dedicated efforts to understand the cell division process of Xac. Since perturbation of cell division is an excellent strategy to inhibit bacterial growth and infection, we have developed compounds that target the main protein constituent of the divisional septa. Here, we intend to study a novel polypeptide encoded by a hypothetical ORF, XAC3407, which apparently is involved with cell division. This ORF was identified in protein-protein analyses in which we used as bait Xac ZapA, a well-known cell division/FtsZ-stabilizer factor. XAC3407 was expressed in Xac by a fusion with Green Fluorescent Protein (GFP) in its N- terminal and visualized in fluorescent microscopy. The sub-cellular localization pattern observed for this ORF was a perpendicular bar to the longitudinal axis of the cell, arranged in the center of the rod, the middle of the cell, co-localizing with the division septum. In bioinformatic analysis, we observed that this ORF is annotated as ZapB in KEGG database, besides, it also showed high similarity and identity with proteins from related organisms annotated as ZapB. However, in alignment with ZapB from Escherichia coli it presented low identity/similarity, but they display the same sub-cellular localization pattern...